Formy obrotu ziemią rolniczą w Polsce - Maśniak, Jacek (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The aim of the article is to introduce the importance of individual forms of agricultural land turnover. The analysis covers land turnover defined in narrow scope, including only ownership changes of land possession. The research covers the span 1990–2006. The analysis shows, that in examined period the importance of market and non-market agricultural land turnover changed. In the year 1990 non-market transaction amounted to 71% of total agricultural land transactions, and next, starting from the mid-nineties the share of them stabilised at the level of 45–50%. The liberalization of the agricultural land turnover after 1990 had revived private land market. In 2006 82% of market transactions was reached between private individuals, and in 18% public sector participated.